The First RE100 University in Japan-Responsible Consumption and Production of Energy - Sachihiko Harashina (Journal of Sustainability Perspectives, 2022)
Proactive use of renewable energy is required to create a sustainable energy society, which is related to the various goals of the SDGs such as SDG7 on energy, SDG13 on climate action and SDG12 on responsible consumption and production. Addressing the energy issue as a university is significant in two ways. First, universities can influence other entities, such as businesses, local governments etc. Second, universities have a mission to educate students who can transform society into a sustainable one. In a press release of 2014, I announced the intention of making CUC the first 100% renewable energy university in Japan, which was a voluntary action. After becoming the president in 2017, this became an official project of the university, enabling investment in the necessary facilities. From the experience of having achieved our goal, I will explain the factors leading to our success and the lessons applicable to other universities.Keyword: SDGs, responsible university, zero carbon campus, renewable energy, heart-ware